The woman in the library eaudiobook - Gentill, Sulari (Dreamscape Media, 2022)
The ornate reading room at the Boston Public Library is quiet—until the tranquility is shattered by a woman's terrified scream. Security guards take charge immediately, instructing everyone inside to stay put until the threat is identified and contained. While they wait for the all-clear, four strangers, who'd happened to sit at the same table, pass the time in conversation, and friendships are struck. Each has his or her own reasons for being in the reading room that morning—it just happens that one is a murderer. Award-winning author Sulari Gentill delivers a sharply thrilling listen with this unexpectedly twisty literary adventure that examines the complicated nature of friendship and reveals that words can be the most treacherous weapons of all.